2009
DOI: 10.1590/s0004-282x2009000200031
|View full text |Cite
|
Sign up to set email alerts
|

Angioarchitecture and clinical presentation of brain arteriovenous malformations

Abstract: -The purpose of this study was to correlate the angioarchitecture of brain arteriovenous malformations (AVM) with their clinical presentation. A total of 170 patients with AVM 78 males and 92 females, were studied. Univariate and multivariate analyses were conducted in order to test the associations between morphological features and clinical presentation. The most frequent clinical presentations at diagnosis were hemorrhage in 89 (52%) patients, headache in 79 (46%), focal neurological deficit in 54 (32%), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
0
14
0
4
Order By: Relevance
“…Only a few articles have exclusively studied the angioarchitectural characteristics of BAVMs associated with clinical presentation of seizures. 3,18 Our experience showed that certain angioarchitectural characteristics are more often associated with seizure presentation. These include cortical location; features indicative of high flow such as the presence of a fistulous component in the nidus and perinidal angiogenesis; and features indicative of venous congestion, such as a long pial course of the draining vein, pseudophlebitic pattern, and venous outflow stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only a few articles have exclusively studied the angioarchitectural characteristics of BAVMs associated with clinical presentation of seizures. 3,18 Our experience showed that certain angioarchitectural characteristics are more often associated with seizure presentation. These include cortical location; features indicative of high flow such as the presence of a fistulous component in the nidus and perinidal angiogenesis; and features indicative of venous congestion, such as a long pial course of the draining vein, pseudophlebitic pattern, and venous outflow stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that large and medium nidus sizes (3-6 cm and Ͼ6 cm, respectively) were positively correlated with seizure occurrence, whereas small nidus size (Ͻ3 cm) was negatively correlated with presentation with seizures. 18 A large BAVM may be more likely to present with seizures because the overall "sump effect" of the BAVM may be more prominent, compared with a small BAVM. Seizure occurrence may also be related to the larger volume of tissue in the circumferential vicinity of the BAVM, with a higher likelihood of affecting a potentially ictogenic zone, or it may be due to a more widespread hypoxemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this pattern is gradually changing. Increasing availability of noninvasive imaging methods, mainly MRI, have led to more and more frequent detection of unruptured and even incidental AVMs (4) . Cerebral arteriovenous malformations are amenable to various treatment modalities which include the following either individually or in combination: surgical removal (resection), radiosurgery and endovascular embolization (5) .…”
Section: Spetzler and Martinmentioning
confidence: 99%